Sosiologi Hukum Dan Hubungan Hukum Terhadap Perubahan Sosial - Wibowo, Iqbal Harry; Siregar, Achmad Zulfikar (Jurnal Sosial Politik dan Hukum, 2024)
Simple and modern society urgently need a legal system that regulate the interaction between one another. Organized community life based on social norms and regulations established institutional. However, other forms of social life does not always run normally in accordance with social norms and regulations existing institutional. Thus social change is a necessity in society. Social change is closely related to the law. Law has a very close correlation with social change as between law and social change have interdependencies. On the one hand, the social changes must be in line with the rules of law, and on the other hand, precisely the rules of law which must conform to certain social changes.